2011
DOI: 10.1007/s10072-011-0872-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic guanosine treatment on hippocampal damage and cognitive impairment of rats submitted to chronic cerebral hypoperfusion

Abstract: Chronic cerebral hypoperfusion contributes to a cognitive decline related to brain disorders. Its experimental model in rats is a permanent bilateral common carotid artery occlusion (2VO). Overstimulation of the glutamatergic system excitotoxicity due to brain energetic disturbance in 2VO animals seems to play a pivotal role as a mechanism of cerebral damage. The nucleoside guanosine (GUO) exerts extracellular effects including antagonism of glutamatergic activity. Accordingly, our group demonstrated several n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 82 publications
1
30
0
Order By: Relevance
“…Previously, we reported that chronic oral GUO treatment was also able to increase ADO plasma levels [7]. Some works in the literature have focused attention on the interplay of extracellular ADO and GUO levels.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Previously, we reported that chronic oral GUO treatment was also able to increase ADO plasma levels [7]. Some works in the literature have focused attention on the interplay of extracellular ADO and GUO levels.…”
Section: Discussionmentioning
confidence: 97%
“…Determination of the purines concentration in CSF, blood plasma, and brain structures was performed using the methodology of HPLC described previously [7]. The injected sample volume was 0.02 ml.…”
Section: Hplcmentioning
confidence: 99%
See 3 more Smart Citations